2019
DOI: 10.1038/s41419-019-1773-0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-phenyl-(2,4-dihydroxypyrimidine-5-sulfonamido) phenylurea-based thymidylate synthase (TS) inhibitor as a novel multi-effects antitumor drugs with minimal toxicity

Abstract: Thymidylate synthase (TS) is a hot target for tumor chemotherapy, and its inhibitors are an essential direction for anti-tumor drug research. To our knowledge, currently, there are no reported thymidylate synthase inhibitors that could inhibit cancer cell migration. Therefore, for optimal therapeutic purposes, combines our previous reports and findings, we hope to obtain a multi-effects inhibitor. This study according to the principle of flattening we designed and synthesized 18 of N -ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…5fluorouracil was introduced in 1957 (Heidelberger et al, 1957), and TS inhibitors are currently approved in treatment of breast, colon and rectum, gastric, gastroesophageal junction, and pancreatic adenocarcinomas as well as nonsquamous, non-small cell lung cancers. Still, studies continue to investigate TS catalysis and attempt to improve the functionality of TS inhibitors (Kholodar et al, 2018;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…5fluorouracil was introduced in 1957 (Heidelberger et al, 1957), and TS inhibitors are currently approved in treatment of breast, colon and rectum, gastric, gastroesophageal junction, and pancreatic adenocarcinomas as well as nonsquamous, non-small cell lung cancers. Still, studies continue to investigate TS catalysis and attempt to improve the functionality of TS inhibitors (Kholodar et al, 2018;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of cell cycle and apoptosis studies were found to be in agreement with the reported literature. 34,35 In Silico Physicochemical and Pharmacokinetics Studies. The development of new drugs has been a costly, risky and challenging venture with a low victory success rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thymidylate synthase is involved in the process of DNA replication and repair, and controls the synthesis of apoptosis‐related proteins. [ 98 ] Therefore, thymidylate synthase is considered as an important target of anticancer drugs. Based on this principle, many famous pyrimidine‐based NADs have been synthesized, including 5‐fluorouracil and 5‐(trifluoromethyl)‐uracil (Figure 8).…”
Section: Applications Of Artificial Nucleobases In Molecular Medicinementioning
confidence: 99%